The Implementation of Restorative Justice in the Rehabilitation of Drug Offenders: A Case Study of Decision Number 7/Pid.Sus/2021/PN.Tmt - Apriliawan, Hendri; Wirogioto, Ali Johardi; Saefullah, Saefullah (Justice Voice, 2025)
The restorative justice approach in the criminal justice system has emerged as an alternative in addressing drug abuse, focusing on rehabilitation rather than imprisonment. This study evaluates the implementation of restorative justice in Decision No. 7/Pid.Sus/2021/PN.Tmt, examining the role of the legal system in determining whether drug abusers qualify for rehabilitation. A juridical-normative and juridical-sociological approach was employed to analyze regulations and judicial practices related to rehabilitation. The key findings indicate that rehabilitation is a more effective alternative to imprisonment, considering the integrated assessment conducted by the National Narcotics Agency (BNN) to determine the severity of addiction. However, the main challenges in implementing restorative justice include limited rehabilitation facilities, inconsistency in judicial decisions, and social stigma against drug users. This study concludes that harmonizing regulations and enhancing law enforcement officers’ understanding of restorative justice are essential to optimizing rehabilitation implementation in Indonesia’s legal system. With a more inclusive approach, the judiciary can adopt a more humane and effective method in handling drug abuse cases.